The Influence of Talking Chips Technique towards Students’ Speaking Ability at the Tenth Class of SMA Negeri 3 Bandar Lampung - Anum, Adelina (International Journal Corner of Educational Research, 2022)
The objectives of this research were to know and describe whether there is an influence of talking chips technique towards students’ speaking ability or not and to know and to describe whether the average score of students’ speaking ability who learn speaking through talking chip technique is higher than those who learn speaking through drilling technique. This research was conducted of tenth class at SMA Negeri 3 Bandar Lampung. In this research, the writer used experimental method. In determining the sample, the writer used cluster random sampling technique because the average of each was homogenous. The writer took 2 classes of ten classes as the samples in this research. In collecting the data the writer used the speaking test. To analyze the data, the writer used formula. The result shows that there is positive and significant influence of talking chips technique towards students’ speaking ability at the tenth class of SMA Negeri 3 Bandar Lampung. The students who were taught speaking through talking chips technique get higher score than those who were taught speaking through drilling technique. It can be seen from calculation of the result of the hypothesis testing and average score of the experimental class that was higher than the control class. The average score of the experimental class is 72.67 and the average score of the control class is 67. It also can be seen at the significant level of 0.01 and 0.05 the is higher than (), that is 2.87 > 2.66 for significant level 0.01 and 2.87 > 2.00 for significant level 0.05.